2003
DOI: 10.1258/135763303771005234
|View full text |Cite
|
Sign up to set email alerts
|

Effective delivery of neonatal stabilization education using videoconferencing in Manitoba

Abstract: We compared face-to-face and videoconference delivery of an education programme for health professionals on the subject of neonatal stabilization skills. A pre-test/post-test control group design was used to compare knowledge acquisition and satisfaction between the two modalities. There were no statistically significant differences between delivery modalities for knowledge acquisition. Both groups showed significant gains in knowledge when pre- and post-test scores were compared. Responses to most of the item… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
3

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 5 publications
0
14
0
3
Order By: Relevance
“…The nine comparative studies [12][13][14][15][16][17][18][19][20] further reinforced comparable learning outcomes for face-to-face and telelearning delivery formats. Of note, videoconferencing was the prominent tele-learning method utilised by the majority of the comparative studies.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…The nine comparative studies [12][13][14][15][16][17][18][19][20] further reinforced comparable learning outcomes for face-to-face and telelearning delivery formats. Of note, videoconferencing was the prominent tele-learning method utilised by the majority of the comparative studies.…”
Section: Resultsmentioning
confidence: 98%
“…Of these, four randomised controlled studies [8][9][10][11] and nine comparative studies [12][13][14][15][16][17][18][19][20] were identified as measuring learning outcomes of telelearning versus traditional face-to-face education. The remaining 34 papers were either descriptive observational studies or did not measure tele-learning versus face-to-face education and so were excluded from the review.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…12 Test scores were compared for the control group, those receiving traditional, in-person S.T.A.B.L.E. Instructor shortages, high staff turnover, and the impact of long winters are additional challenges affecting outreach education.…”
Section: Province Of Manitobamentioning
confidence: 99%